qanda-logo
search-icon
Símbolos
Problema
solution-image
$\left(x+11\right)\left(x-11\right)$ $=$ $\left(3x+4\right)\left(3x-4\right)$ $=a$ $\left(a+b\right)\left(a-b\right)$ $=$ $\left(x+7\right)\left(x+9\right)$ $=$ $\left(2x+1\right)\left(2x+3\right)$ $=$ $\left(x+5\right)\left(x-4\right)$ $=$ $\left(a+10\right)^{2}=$ $\left(b-5\right)^{2}$ $=$ $\left(2x-6y\right)^{2}=$
Bachillerato
Aritmética y álgebra
Búsquedas: 114
Solución
answer-user-profile-image
Profesor de Qanda - jhostin
answer-reply-image
Listo. Un gusto :)
answer-user-profile-image
Estudiante
Muchas gracias ? en serio